1988
DOI: 10.1038/jcbfm.1988.117
|View full text |Cite
|
Sign up to set email alerts
|

Origins and Pathways of Cerebrovascular Vasoactive Intestinal Polypeptide-Positive Nerves in Rat

Abstract: Summary: In order to clarify the origins and pathways of vasoactive intestinal polypeptide (VIP)-containing nerve fibers in cerebral blood vessels of rat, denervation exper iments and retrograde axonal tracing methods (true blue) were used. Numerous VIP-positive nerve cells were rec ognized in the sphenopalatine ganglion and in a mini-gan glion (internal carotid mini-ganglion) located on the in ternal carotid artery in the carotid canal, where the para sympathetic greater superficial petrosal nerve is joined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
96
0
1

Year Published

1991
1991
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(102 citation statements)
references
References 33 publications
5
96
0
1
Order By: Relevance
“…, 1993). Neuropeptide Y and vasoac tive intestinal polypeptide are also present as trans mitters in the parasympathetic nerves (Suzuki et al, 1988(Suzuki et al, , 1990b) and exert their vasoconstrictor or dilator action without contribution from endothe lium-linked mechanisms (Uddman and Edvinsson, 1989). Other as yet unidentified transmitters may be present in these nerves with an influence on vascu lar tone that may be endothelium dependent.…”
mentioning
confidence: 99%
“…, 1993). Neuropeptide Y and vasoac tive intestinal polypeptide are also present as trans mitters in the parasympathetic nerves (Suzuki et al, 1988(Suzuki et al, , 1990b) and exert their vasoconstrictor or dilator action without contribution from endothe lium-linked mechanisms (Uddman and Edvinsson, 1989). Other as yet unidentified transmitters may be present in these nerves with an influence on vascu lar tone that may be endothelium dependent.…”
mentioning
confidence: 99%
“…Uni-or bilateral sphenopalatine ganglionec tomy or sham operation was performed by a zygomatico lacrimal approach, as described by Rosen et al (1940) and more recently by Suzuki et al (1988). The zygomatic bone was exposed through a skin incision and cut at both extremities; the masseter muscle was then retracted in order to uncover the fifth nerve trunk, which was cleaned…”
Section: Sphenopalatine Ganglionectomymentioning
confidence: 99%
“…In the rat, it has been elegantly shown that VIP positive nerves originate mainly from the SPG (Hara et aI., 1985;Suzuki et al, 1988) and to a lesser extent the otic ganglia to innervate the circle of Willis and its branches, and from the internal carotid miniganglion to innervate the internal ca rotid artery (Suzuki et aI., 1988). Based on the co existence of VIP and AChE in cerebrovascular fi bers and in the SPG (Kobayashi et aI., 1983;ltakura et aI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the otic ganglion contains many VIPergic perikarya and is known to innervate brain vasculature [31,33]. Whether this ganglion projects to the pineal gland is at the moment unknown.…”
mentioning
confidence: 99%